Anticancer activity of an Artemisia annua L. hydroalcoholic extract on canine osteosarcoma cell lines. (20th December 2022) - Salaroli, Roberta; Andreani, Giulia; Bernardini, Chiara; Zannoni, Augusta; La Mantia, Debora; Protti, Michele; Forni, Monica; Mercolini, Laura; Isani, Gloria
Abstract: Since ancient times, Artemisia annua ( A. annua ) has been used as a medicinal plant in Traditional Chinese Medicine. In addition, recent studies have investigated the cytotoxic effects of A. annua extracts towards cancer cells. The leading aim of the present research is to evaluate the cytotoxic effects of an hydroalcoholic extract of A. annua on two canine osteosarcoma (OSA) cell lines, OSCA-8 and OSCA-40, focusing on the possible involvement of ferroptosis. The quantitative determination of artemisinin concentration in the extract, culture medium and OSA cells was carried out through the use of an instrumental analytical method based on liquid chromatography coupled with spectrophotometric detection and tandem mass spectrometry (LC-DAD-MS/MS). OSCA-8 and OSCA-40 were exposed to different dilutions of the extract for the EC50 calculation then the uptake of artemisinin by the cells, the effects on the cell cycle, the intracellular iron level, the cellular morphology and the lipid oxidation state were evaluated. A concentration of artemisinin of 63.8 ± 3.4 μg/mL was detected in the extract. A dose-dependent cytotoxic effect was evidenced. In OSCA-40 alterations of the cell cycle and a significantly higher intracellular iron content were observed. In both cell lines the treatment with the extract was associated with lipid peroxidation and with the appearance of a "ballooning" phenotype suggesting the activation of ferroptosis. In conclusion the A. annua idroalcoholic extract utilized in this study showed anticancer activity on canine OSA cell lines that could be useful in treating drug resistant canine OSAs. Graphical abstract: Unlabelled Image Highlights: Artemisinin concentration was measured using MEPS-LC-DAD-MS/MS Osteosarcoma cell lines OSACA-8 and OSCA-40 actively took up artemisinin The exposure to A. annua extract induced a decrease in G0/G1 and an increase in sub G0/G1 phase in OSCA-40 cells Artemisia annua hydroalcoholic extract triggered the appearance of a "ballooning" phenotype The intracellular iron content influences the sensitivity of cells to ferroptosis